Book Reviews / Rezensionen - Malcolm Sawyer; Artur Tarassow; Christian Schoder; Marc Lavoie; Engelbert Stockhammer; Martin Schürz (Intervention. European Journal of Economics and Economic Policies, 2009)
Books reviewed: Robert Leeson (ed.) (2008): The Keynesian Tradition, Basingstoke Robert Leeson (ed.) (2008): The Anti-Keynesian Tradition, Basingstoke Stefan Ederer (2008): Einkommensverteilung und gesamtwirtschaftliche Nachfrage in Österreich und den Niederlanden, Marburg Neva Goodwin/Julie A. Nelson/Frank Ackerman/Thomas Weisskopf (2009): Microeconomics in Context, 2nd edition, Armonk Neva Goodwin/Julie A.Nelson/Jonathan Harris (2009): Macroeconomics in Context, Armonk Mary Gregory, Wiemer Salverda, Ronald Schettkat (eds.): Services and Employment. Explaining the U.S.-European Gap, Princeton Costabile, Lilia (ed.) (2008): Institutions for Social Well Being. Alternatives for Europe, Basingstoke
Keywords: 330